2015
DOI: 10.1111/jfs.12196
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Essential Oils on Clostridium perfringens Type A Inoculated in Mortadella

Abstract: The antimicrobial activity of essential oils on Clostridium perfringens type A and the influence of such oils on mortadella quality were assessed. The anticlostridial effects of several essential oils and their combinations were identified and some essential oils and their combinations were selected for further study in mortadellas supplemented with 75 ppm sodium nitrite and inoculated with C. perfringens. The growth of C. perfringens in mortadella was not inhibited by nitrite (control treatments of 75 and 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
5
5
0
Order By: Relevance
“…Observing the PCA (Figure 1A) of the essential oils combinations, oregano and clove oils are highlighted with the greatest contribution to the bactericidal effect of the different tested combinations. These results were similar to those obtained by Dias and coauthors [13], who found that blends containing the highest ratios of oregano essential oil were more effective against C. perfringens type A. The phenolic constituents present in essential oils alter the permeability and break the cell membrane leading to the inhibition of functional properties and leakage of the internal content, leading to cell death [25].…”
Section: Minimal Bactericidal (Mbc) and Sporicidal Concentration (Msc) Of Essential Oils And Its Combinationssupporting
confidence: 90%
See 2 more Smart Citations
“…Observing the PCA (Figure 1A) of the essential oils combinations, oregano and clove oils are highlighted with the greatest contribution to the bactericidal effect of the different tested combinations. These results were similar to those obtained by Dias and coauthors [13], who found that blends containing the highest ratios of oregano essential oil were more effective against C. perfringens type A. The phenolic constituents present in essential oils alter the permeability and break the cell membrane leading to the inhibition of functional properties and leakage of the internal content, leading to cell death [25].…”
Section: Minimal Bactericidal (Mbc) and Sporicidal Concentration (Msc) Of Essential Oils And Its Combinationssupporting
confidence: 90%
“…Inoculum maintenance was done according to Dias and coauthors [13]. Inoculum standardization (10 7 CFU/mL) was performed with a growth curve (OD 600 nm) and counting on BHI agar plates, with overlay, supplemented with 0.5% glucose and incubated at 37 °C for 24 h.…”
Section: Microorganism Standardization and Maintenance Of The Inoculummentioning
confidence: 99%
See 1 more Smart Citation
“…This study also demonstrated T. vulgaris to be bactericidal but at a much lower concentration (0Á50 mg ml −1 ). In another study, a handful of essential oils were tested against C. perfringens (Dias et al 2015). The authors of that study found that C. limon, C. paradisi, O. basilicum, R. officinalis and Z. officinale showed no antibacterial activity (MIC) or cidal activity (MBC).…”
Section: Discussionmentioning
confidence: 99%
“…These two compounds showed an MIC value of 0Á38 mg ml −1 individually against C. perfringens with an MBC value of 0Á75 mg ml −1 each. Dias et al (2015) also tested four essential oils (C. citratus, O. vulgare, S. aromaticum and T. vulgaris) against C. perfringens in various ratios of a combination of three essential oils. That study demonstrated that no synergy was found in any of the combinations tested which somewhat supports the data seen in this current study when two oils were combined.…”
Section: Discussionmentioning
confidence: 99%